Safety and efficacy of lumen-apposing metal stents versus plastic stents to treat walled-off pancreatic necrosis: systematic review and meta-analysis - Chandrasekhara, Vinay; Barthet, Marc; Devière, Jacques; Bazerbachi, Fateh; Lakhtakia, Sundeep; Easler, Jeffrey J.; Peetermans, Joyce A.; McMullen, Edmund; Gjata, Ornela; Gourlay, Margaret L.; Abu Dayyeh, Barham K. (Endoscopy International Open, 2020)
Background and study aims Lumen-apposing metal stents (LAMS) are increasingly used for drainage of walled-off pancreatic necrosis (WON). Recent studies suggested greater adverse event (AE) rates with LAMS for WON. We conducted a systematic review and meta-analysis to compare the safety and efficacy of LAMS with double-pigtail plastic stents (DPPS) for endoscopic drainage of WON. The primary aim was to evaluate stent-related AEs.Methods In October 2019, we searched the Ovid (Embase, MEDLINE, Cochrane) and Scopus databases for studies assessing a specific LAMS or DPPS for WON drainage conducted under EUS guidance. Safety outcomes were AE rates of bleeding, stent migration, perforation, and stent occlusion. Efficacy outcomes were WON resolution and number of procedures needed to achieve resolution. A subanalysis including non-EUS-guided cases was performed.Results Thirty studies including one randomized controlled trial (total 1,524 patients) were analyzed. LAMS were associated with similar bleeding (2.5 % vs. 4.6 %, P = 0.39) and perforation risk (0.5 % vs. 1.1 %, P = 0.35) compared to DPPS. WON resolution (87.4 % vs. 87.5 %, P = 0.99), number of procedures to achieve resolution (2.09 vs. 1.88, P = 0.72), stent migration (5.9 % vs. 6.8 %, P = 0.79), and stent occlusion (3.8 % vs. 5.2 %, P = 0.78) were similar for both groups. Inclusion of non-EUS-guided cases led to significantly higher DPPS bleeding and perforation rates.Conclusions LAMS and DPPS were associated with similar rates of AEs and WON resolution when limiting analysis to EUS-guided cases. Higher bleeding rates were seen in historical studies of DPPS without EUS guidance. Additional high-quality studies of WON treatment using consistent outcome definitions are needed.